Determinants of Islamic Financial Institutions on Poverty Reduction: A Systematic Review - Al Afif, Rafiq Azzam; Esaputra, Ahmad Baihaqi; Rahmatdi; Ahmadi, Mirzam Arqy (Universitas Muhammadiyah Yogyakarta, 2025)
This study explores the multifaceted determinants of Islamic Financial Institutions (IFIs) in alleviating poverty by employing a qualitative meta-synthesis approach guided by the ENTREQ protocol. The research synthesizes findings from 23 scholarly articles indexed in Scopus to identify key internal and external factors influencing IFI performance in poverty alleviation. These determinants are systematically categorized into a strategic quadrant model: internal-structural, internal-behavioural, external-structural, and external-behavioural. Internal-structural elements such as institutional capacity, operational models, access to capital, and adherence to Islamic values significantly affect the success of IFIs, while internal-behavioural dimensions highlight the roles of innovation, religiosity, and community-based initiatives. Externally, the legal and policy environment, cultural dynamics, public perception, and economic conditions emerge as critical influences on IFIs’ outreach and effectiveness. The findings reveal that IFIs often face challenges in maintaining their developmental focus due to resource limitations, regulatory gaps, and competitive financial landscapes. Nonetheless, when grounded in Islamic ethical principles and supported by appropriate institutional frameworks, IFIs demonstrate a strong potential to deliver inclusive financial services and uplift marginalized communities. The novelty of this study lies in its integrative approach to consolidating diverse themes into a coherent analytical framework, offering actionable insights for practitioners, regulators, and scholars. It emphasizes that successful poverty alleviation through IFIs requires a synchronized interplay of ethical commitment, institutional readiness, policy support, and grassroots participation. The results contribute to the development of strategic recommendations for enhancing the role of Islamic finance in addressing poverty across different socio-economic and regulatory contexts.